Fluopsin C induces oncosis of human breast adenocarcinoma cells - Ma Li-sha; Jiang Chang-you; Cui Min; Lu Rong; Liu Shan-shan; Zheng Bei-bei; Li Lin; Li Xia (Acta Pharmacologica Sinica, 2016)
Aim: Fluopsin C, an antibiotic isolated from Pseudomonas jinanesis, has shown antitumor effects on several cancer cell lines. In the current study, the oncotic cell death induced by fluopsin C was investigated in human breast adenocarcinoma cells in vitro. Methods: Human breast adenocarcinoma cell lines MCF-7 and MD-MBA-231 were used. The cytotoxicity was evaluated using MTT assay. Time-lapse microscopy and transmission electron microscopy were used to observe the morphological changes. Cell membrane integrity was assessed with propidium iodide (PI) uptake and lactate dehydrogenase (LDH) assay. Flow cytometry was used to measure reactive oxygen species (ROS) level and mitochondrial membrane potential (Δψm). A multimode microplate reader was used to analyze the intracellular ATP level. The changes in cytoskeletal system were investigated with Western blotting and immunostaining. Results: Fluopsin C (0.5-8 μmol/L) reduced the cell viability in dose- and time-dependent manners. Its IC50 values in MCF-7 and MD-MBA-231 cells at 24 h were 0.9 and 1.03 μmol/L, respectively. Fluopsin C (2 μmol/L) induced oncosis in both the breast adenocarcinoma cells characterized by membrane blebbing and swelling, which was blocked by pretreatment with the pan-caspase inhibitor Z-VAD-fmk. In MCF-7 cells, fluopsin C caused PI uptake into the cells, significantly increased LDH release, induced cytoskeletal system degradation and ROS accumulation, decreased the intracellular ATP level and Δψm. Noticeably, fluopsin C exerted comparable cytotoxicity against the normal human hepatocytes (HL7702) and human mammary epithelial cells with the IC50 values at 24 h of 2.7 and 2.4 μmol/L, respectively. Conclusion: Oncotic cell death was involved in the anticancer effects of fluopsin C on human breast adenocarcinoma cells in vitro. The hepatoxicity of fluopsin C should not be ignored.